2021
DOI: 10.54651/agri.2021.01.09
|View full text |Cite
|
Sign up to set email alerts
|

Phytosanitary condition of spring wheat crops depending on plowing of different and planar loosening

Abstract: The article presents the stationary experience of the Department of General Agriculture of the Uman National University of Horticulture, where during 2014–2016. The phytosanitary condition in crops of spring wheat was studied. The culture was located in a five-field crop rotation after spring rape. Factor A in the experiment was the soil cultivation methods represented by plowing and plow-cutting cultivation, and factor B – the depths of these cultivations — 15–17, 20–22, and 25–27 cm. The objects of research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In contrast, Copper et al (2020) have found that organic carbon content, microbiological activity and bulk density of soil are not influenced by soil tillage system [5]. A majority of researchers agree that different systems of reduced soil tillage increase the occurrence of slugs [5], weeds and diseases, including wheat diseases [6][7][8][9]. Many studies about the efficacy of different soil tillage systems have been conducted throughout the world, but obtained results are still contradictory; therefore, the importance of soil tillage system as part of sustainable cropping system is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Copper et al (2020) have found that organic carbon content, microbiological activity and bulk density of soil are not influenced by soil tillage system [5]. A majority of researchers agree that different systems of reduced soil tillage increase the occurrence of slugs [5], weeds and diseases, including wheat diseases [6][7][8][9]. Many studies about the efficacy of different soil tillage systems have been conducted throughout the world, but obtained results are still contradictory; therefore, the importance of soil tillage system as part of sustainable cropping system is still unclear.…”
Section: Introductionmentioning
confidence: 99%